Supramolecular Self-Assembled Nanostructures for Cancer Immunotherapy - Zichao Huang; Zichao Huang; Wantong Song; Wantong Song; Xuesi Chen; Xuesi Chen; Xuesi Chen (Frontiers in Chemistry, 2020)
Functional materials and nanostructures have been widely used for enhancing the therapeutic potency and safety of current cancer immunotherapy. While profound nanostructures have been developed to participate in the development of cancer immunotherapy, the construction of intricate nanostructures with easy fabrication and functionalization properties to satisfy the diversified requirements in cancer immunotherapy are highly required. Hierarchical self-assembly using supramolecular interactions to manufacture organized architectures at multiple length scales represents an interesting and promising avenue for sophisticated nanostructure construction. In this mini-review, we will outline the recent progress made in the development of supramolecular self-assembled nanostructures for cancer immunotherapy, with special focus on the supramolecular interactions including supramolecular peptide assembly, supramolecular DNA assembly, lipid hydrophobic assembly, host-guest assembly, and biomolecular recognition assembly.